An Evaluation of the Use of Educational Resource Guides for Military Students in Public Schools. (3rd April 2017) - Castillo, Berenice; Capp, Gordon; Moore, Hadass; De Pedro, Kris; Pineda, Diana; Benbenishty, Rami; Astor, Ron Avi
ABSTRACT: Most public school staff are unaware of the presence of military-connected students in their schools. The Building Capacity Consortium aimed to increase awareness of military-connected students and meet their needs in schools. The Consortium developed a series of guidebooks to share evidence-based and homegrown strategies to support military-connected students and their families. Educational guidebooks are frequently used for training, but few are evaluated for their usefulness. This evaluation included a survey of 649 recipients of resource guides and presents their feedback. Results indicate that the resource guides were well received. Recommendations for further dissemination of these guides are discussed.